Association of obesity with osteoporotic fracture risk in individuals with bone metabolism-related conditions: a cross sectional analysis - Yang, Guijun; Jiang, Hejun; Xie, Dan; Yuan, Shuhua; Wu, Jinhong; Zhang, Jing; Zhang, Lei; Yuan, Jiajun; Lin, Jilei; Chen, Jiande; Yin, Yong (Frontiers in Nutrition, 2024)
This study aimed to investigate the individual and composite associations of different indices of obesity on osteoporotic fractures at three different sites among individuals affected by conditions influencing bone metabolism. 5377 participants were included from the National Health and Nutrition Examination Survey (NHANES), a national cross-sectional survey. BMI and WC were used separately and in combination to evaluate the presence of obesity. Obesity was defined as BMI ≥ 30 kg/m², WC ≥ 88 cm in females, and WC ≥102 cm in males. Associations between obesity and osteoporotic fractures were assessed using multivariable logistic regression and OR curves. Associations modified by age, sex, race, and alcohol consumption were also evaluated. In multivariable logistic regression analyses, we found that BMI, WC, BMI defining obesity, and WC defining obesity were negatively associated with hip fracture (all P < 0.05). However, harmful associations between WC and BMI defining obesity and spine fracture were found (all P < 0.05). OR curves revealed that BMI and WC had a linear relationship with hip and spine fractures (all P for non-linearity > 0.05). Further analyses showed that the highest WC quartile was harmfully associated with a higher risk of spine fractures (P < 0.05). Obese participants diagnosed by both BMI and WC were less likely to have hip fractures but more likely to have spine fractures (all P for trend < 0.05). A significant interaction between age (Ref: age < 50 years) and BMI and WC was detected for hip fractures (all P for interaction < 0.05). In people with conditions influencing bone metabolism, obesity diagnosed by BMI and WC was associated with a lower risk of hip fracture, while obesity diagnosed by BMI and the highest WC quartile were associated with a higher risk of spine fracture.